Colonization by orchid mycorrhizal fungi primes induced systemic resistance against necrotrophic pathogen - Pujasatria, Galih Chersy; Miura, Chihiro; Yamaguchi, Katsushi; Shigenobu, Shuji; Kaminaka, Hironori (Frontiers in Plant Science, 2024)
Orchids and arbuscular mycorrhiza (AM) plants evolved independently and have different structures and fungal partners, but they both facilitate nutrient uptake. Orchid mycorrhiza (OM) supports orchid seed germination, but unlike AM, its role in disease resistance of mature plants is largely unknown. Here, we examined whether OM induces systemic disease resistance against a necrotrophic pathogen in a similar fashion to AM. We investigated the priming effect of mycorrhizal fungi inoculation on resistance of a terrestrial orchid, Bletilla striata, to soft rot caused by Dickeya fangzhongdai. We found that root colonization by a compatible OM fungus primed B. striata seedlings and induced systemic resistance against the infection. Transcriptome analysis showed that priming was mediated by the downregulation of jasmonate and ethylene pathways and that these pathways are upregulated once infection occurs. Comparison with the reported transcriptome of AM fungus–colonized rice leaves revealed similar mechanisms in B. striata and in rice. These findings highlight a novel aspect of commonality between OM and AM plants in terms of induced systemic resistance.